JUSTICE FOR SALE: AN ANALYSIS OF ELECTORAL JURISPRUDENCE IN NIGERIA - Adom, Amasekaven; Ahoo, Terhile Jude; Kete, Tartor Titus (African Journal of Social and Behavioural Sciences, 2024)
In Nigeria, every electoral year is riddled with grievances, disputes, and discontentment regarding the processes, procedures and outcome of elections. Those who feel unfairly treated proceed to the tribunal to seek redress, and the more resources a petitioner has, the higher their ability to hire competent legal personnel to defend their case(s). This is also the situation with judges who use their position to acquire as much resources as they can. This article explored electoral jurisprudence in Nigeria, focusing particularly on the relationship between justice and the electoral tribunal in Nigeria, the character of election tribunal and election petition in Nigeria, and electoral jurisprudence and commodification of justice in Nigeria. The study anchored on the social conflict theory. It employed secondary data from the internet, textbooks and other sources of information. Data was analyzed qualitatively. Findings showed that Election Tribunal in Nigeria serve as a crucial institution for resolving disputes regarding the validity of elections. However, electoral jurisprudence in Nigeria is plagued by issues such as technicalities in the judiciary, corruption, and political interference, which lead to the commodification of justice and undermine public trust in the legal system. The paper recommends policy reforms, entrenchment of professional conduct by legal practitioners, and promotion of judicial independence as ways to overcome the imbalances in Nigeria’s electoral jurisprudence.